Pilot Study Exploring Lung Allograft Surfactant Protein A (SP‐A) Expression in Association With Lung Transplant Outcome. Issue 10 (5th September 2013) - D'Ovidio, F.; Kaneda, H.; Chaparro, C.; Mura, M.; Lederer, D.; Di Angelo, S.; Takahashi, H.; Gutierrez, C.; Hutcheon, M.; Singer, L. G.; Waddell, T. K.; Floros, J.; et al.
Abstract Primary graft failure and chronic lung allograft dysfunction (CLAD) limit lung transplant long–term outcomes. Various lung diseases have been correlated with surfactant protein (SP) expression and polymorphisms. We sought to investigate the role of SP expression in lung allografts prior to implantation, in relation to posttransplant outcomes. The expression of SP‐(A, B, C, D) mRNA was assayed in 42 allografts. Posttransplant assessments include pulmonary function tests, bronchoscopy, broncho‐alveolar lavage fluid (BALF) and biopsies to determine allograft rejection. BALF was assayed for SP‐A, SP‐D in addition to cytokines IL‐8, IL‐12 and IL‐2. The diagnosis of CLAD was evaluated 6 months after transplantation. Lung allografts with low SP‐A mRNA expression prior to implantation reduced survival (Log‐rank p < 0.0001). No association was noted for the other SPs. Allografts with low SP‐A mRNA had greater IL‐2 (p = 0.03) and IL‐12 (p < 0.0001) in the BALF and a greater incidence of rejection episodes (p = 0.003). Levels of SP‐A mRNA expression were associated with the SP‐A2 polymorphisms (p = 0.015). Specifically, genotype 1A1A0 was associated with lower SP‐A mRNA expression (p < 0.05). Lung allografts with low levels of SP‐A mRNA expression are associated with reduced survival. Lung allograft SP‐A mRNA expression appears to be associated with SP‐A gene polymorphisms.